Biomarkers of prostate bladder and testicular cancers: current use in anatomic pathology and future directions - Mariana Andozia Morini; Daniel Abensur Athanazio; Luiza Fadul Gallas; José Maurício Mota; Stephania Martins Bezerra; João Lobo; María Belén Molina Froján; Andres Acosta (Surgical and Experimental Pathology, 2024)
Abstract Urologic pathology is rapidly evolving to adopt growing knowledge of molecular pathways involved in genitourinary neoplasm. Many prognostic and predictive biomarkers are under active research and some of them have been incorporated in clinical practice. In this review, we will discuss recent developments of Molecular Pathology of prostate, bladder and testicular tumors with special emphasis on prognostic and predictive biomarkers.